Managing the exploration-exploitation paradox in healthcare: Three complementary paths to leverage on the digital transformation. Issue 5 (13th July 2018) - Gastaldi, Luca; Appio, Francesco Paolo; Corso, Mariano; Pistorio, Andrea
Abstract : Purpose: The purpose of this paper is to understand how digital technologies can help healthcare organisations and improve the exploration-exploitation paradox over time. The authors explore inputs, processes and outcomes of implementing digital transformation programs and advance four testable propositions. Design/methodology/approach: The authors conducted multiple case studies with embedded units of analysis: digital transformation processes; hospitals; and regional healthcare systems. Primary sources come from 107 semi-structured interviews with key informants within 14 Italian hospitals between 2009 through 2011. Findings: Three complementary paths emerge as fundamental to balance exploratory and exploitatory efforts in healthcare: assets digitalisation within hospitals; digitally based process integration; and disruptive decision-making through analytics. Intra- and inter-path characteristics are discussed to show how digital transformation can both move hospital within the exploration-exploitation space. Research limitations/implications: By its very nature, this study is exploratory. Notwithstanding the number of cases and interviews, its generalisability is limited. Practical implications: Digital transformation programs are fundamental to resolve the tensions raised by the exploration-exploitation paradox. Their implementation leads to better performance (cost reductions, quality improvements). A framework is provided for practitioners to make better decisions. Originality/value: This study sheds new light on how digital technologies are actually adopted and adapted in healthcare contexts. It does it by entailing a longitudinal perspective.